Prognosis of 732 ursodeoxycholic acid‐treated patients with primary biliary cholangitis: A single center follow‐up study from China. Issue 7 (14th November 2018) - Chen, Sha; Duan, Weijia; Li, Min; Li, Shuxiang; Lv, Tingting; Tian, Qiuju; Wang, Qianyi; Wu, Xiaoning; Zhao, Xinyan; Wang, Xiaoming; Wang, Yu; Kong, Yuanyuan; et al.
Abstract: Background and Aim: The impact of male sex and past hepatitis B virus (HBV) infection on survival of primary biliary cholangitis (PBC) are issues at discussion. The aim of the present study was to identify risk factors for transplant‐free survival (TRS) in Chinese PBC patients who received ursodeoxycholic acid (UDCA), with special focus on the impact of male sex and past HBV infection. Methods: We followed up PBC patients who received UDCA at our institute between January 2000 and December 2017 until their death, liver transplantation, or censored on April 1, 2018, by interview and review of medical records. We used Cox proportional hazards model and Kaplan–Meier method. Results: Out of 976 PBC patients, 732 UDCA‐treated patients (female : male = 6.2:1) with required clinical and laboratory data were enrolled in this study. The median follow‐up period were 4.8 years (interquartile range: 2.8–7.1 years). The overall 5‐, 10‐, and 15‐year TRS rates were 86.7% (95% CI: 83.8–88.1), 71.1% (95% CI: 65.0–77.2), and 59.2% (95% CI: 44.5–73.9), respectively. The survival was significantly worse for male patients and older patients (≥ 55 years) (log‐rank test: P < 0.05 for both). On multivariate analysis, male sex, cirrhosis, serum bilirubin, and serum albumin were independent predictors for TRS. There was no significant difference in survivals between patients with ( n = 167) and without ( n = 219) past HBV infection (log‐rank test: P = 0.293). Conclusions: In this large Chinese cohort of UDCA‐treated PBC patients, male sex was associated with shorter survival, whereas past HBV infection was not associated with poorer outcome.